The continuous strength method for the design of hot-rolled steel cross-sections. (15th February 2018) - Yun, X.; Gardner, L.; Boissonnade, N.
Highlights: Numerical modelling of hot-rolled structural steel cross-sections under compression and bending. Derivation of CSM resistance functions for hot-rolled steel cross-sections. Comparison of test and numerical data with CSM and Eurocode 3 resistance predictions. Reliability analysis of CSM and Eurocode 3 design provisions. Abstract: The continuous strength method (CSM) is a deformation-based structural design approach that enables material strain hardening properties to be exploited, thus resulting in more accurate and consistent capacity predictions. To date, the CSM has featured an elastic, linear hardening material model and has been applied to cold-formed steel, stainless steel and aluminium. However, owing to the existence of a yield plateau in its stress-strain response, this model is not well suited to hot-rolled carbon steel. Thus, a tri-linear material model, which can closely represent the stress-strain response of hot-rolled carbon steel, is introduced and incorporated into the CSM design framework. Maintaining the basic design philosophy of the existing CSM, new cross-section resistance expressions are derived for a range of hot-rolled steel structural section types subjected to compression and bending. The design provisions of EN 1993-1-1 and the proposed CSM are compared with experimental results collected from the literature and numerical simulations performed in this paper. Overall, the CSM is found to offer more accurate and consistent predictions than the current design provisions of EN 1993-1-1. Finally, statistical analyses are carried out to assess the reliability level of the two different design methods according to EN 1990 (2002).